Factors Associated With Health Care Utilization of Recurrent Clostridium difficile Infection in New York State. Issue 4 (April 2019) - Mathews, Steven N.; Lamm, Ryan; Yang, Jie; Park, Jihye; Tzimas, Demetrios; Buscaglia, Jonathan M.; Pryor, Aurora; Talamini, Mark; Telem, Dana; Bucobo, Juan C.
Abstract : Background: The incidence of infection due to Clostridium difficile infection (CDI) and subsequent economic burden are substantial. Goals: The impact of changing practice patterns on demographics at risk and utilization of health care resources for recurrence of CDI remains unclear. Study: A total of 291, 163 patients hospitalized for CDI were identified from 1995 to 2014 from the New York SPARCS database. The χ 2 test, the Welch t test, and multivariable logistic regression analysis were performed to evaluate factors related to readmission. Results: Hospital admissions and readmissions for CDI peaked in 2008 at 20, 487 and 13, 795, respectively, and have since decreased (linear trend, 0.9706 and 0.9464, respectively; P <0.0001). In total, 60, 077 (21%) patients required ≥2 admissions. Risk factors for readmission included: age 55 to 74, government insurance, hypertension, diabetes, anemia, hypothyroidism, chronic pulmonary disease, rheumatoid arthritis, renal failure, peripheral vascular disease, and depression (all P <0.05). Trends in surgery showed a similar peak in 2008 at 165 and have since decreased (linear trend, 0.8660; P <0.0001). A total of 1830 (0.63%) patients with CDI underwent surgery, with emergent being more common than elective (71% vs. 29%). Conclusions: Hospital admissions and readmissions for CDI peaked in 2008 and have since been steadily declining. These trends may be secondary to improved diagnostic capabilities and evolving antibiotic regimens. More than 1 in 5 hospitalized patients had at least 1 readmission. Numerous risk factors for these patients have been identified. Although <1% of all patients with CDI undergo surgery, these rates have also been declining. Abstract : Supplemental Digital Content is available in the text.